(untitled) (E Global Congress, 2025)
In today’s interconnected and rapidly changing world, the ability to communicate effectively across cultural and linguistic boundaries has become more vital than ever. English, often regarded as the global lingua franca, plays a critical role in international communication, business, education, and technology. This article explores the growing importance of learning English in the context of globalization and how it opens doors to greater opportunities for individuals and societies.